2008
DOI: 10.3174/ajnr.a1357
|View full text |Cite
|
Sign up to set email alerts
|

Fluorodeoxyglucose–Positron-Emission Tomography, Single-Photon Emission Tomography, and Structural MR Imaging for Prediction of Rapid Conversion to Alzheimer Disease in Patients with Mild Cognitive Impairment: A Meta-Analysis

Abstract: BACKGROUND AND PURPOSE:Patients with mild cognitive impairment (MCI) are at risk for developing Alzheimer disease (AD). To diagnose AD at an early stage, one must develop highly specific and sensitive tools to identify it among at-risk subjects. The purpose of this study was to evaluate and compare the ability of fluorodeoxyglucose-positron-emission tomography (FDG-PET), single-photon emission tomography (SPECT), and structural MR imaging to predict conversion to AD in patients with MCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
106
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(116 citation statements)
references
References 35 publications
(27 reference statements)
5
106
0
5
Order By: Relevance
“…Nevertheless, FDG-PET generally has a higher accuracy than MR imaging for diagnosing early AD 10,11 and for predicting rapid conversion of MCI to early AD. 12 A combination of PET and other biomarkers is important because imaging and CSF biomarkers can improve prediction of conversion from MCI to AD compared with baseline clinical testing. FDG -PET appears to add the greatest prognostic information.…”
Section: Mild Cognitive Impairment Due To Alzheimer Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, FDG-PET generally has a higher accuracy than MR imaging for diagnosing early AD 10,11 and for predicting rapid conversion of MCI to early AD. 12 A combination of PET and other biomarkers is important because imaging and CSF biomarkers can improve prediction of conversion from MCI to AD compared with baseline clinical testing. FDG -PET appears to add the greatest prognostic information.…”
Section: Mild Cognitive Impairment Due To Alzheimer Diseasementioning
confidence: 99%
“…Yuan et al 12 performed a meta-analysis and meta-regression on the diagnostic performance data for MR imaging, SPECT, and FDG-PET in subjects with MCI and reported that FDG-PET performed slightly better than SPECT and structural MR imaging in the prediction of conversion to AD in patients with MCI, while a combination of PET and structural MR imaging improved the diagnostic accuracy of dementia. Kawachi et al 10 also compared the diagnostic performance of FDG-PET and voxel-based morphometry (VBM) on MR imaging in the same group of patients with very mild AD and reported an accuracy of 89% for FDG-PET diagnosis and 83% for VBM-MR imaging diagnosis, while the accuracy of combination FDG-PET and VBM-MR imaging diagnosis was 94%.…”
Section: Combination Of Mr Imaging and Petmentioning
confidence: 99%
“…Yine bu çalışmada MCI hastalarının %81'inde posterior singulat korteks ve hipokampal (temporal) hipometabolizma gösterilmiştir (17). Toplamda 1112 hastayı içeren 24 çalışmalık meta-analizde FDG PET'nin MCI-AH dönüşümünü de öngörebildiğini göstermiştir (18). Hastalık progresyonunu veya tedavi yanıtını takipte FDG PET'nin oturmuş bir klinik endikasyonu bulunmasa da ilk görüntülemeden özellikle 6-12 ay sonra tekrarlanması halinde ilerleyici kognitif bozukluğu olan erken şüpheli veya non-diagnostik vakalarda yararlı olabilmektedir.…”
Section: Alzheimer Hastalığında F-18 Fdg Pozitron Emisyontomografi/biunclassified
“…n Interpretation of abnormal test scores Abnormal biomarker scores increase the likelihood for conversion to AD-type dementia within 3 years by a factor of 2-4 [11][12][13][14]. After an average follow-up of 9 years, approximately 90% of the subjects with a combination of abnormal Ab1-42 and tau in CSF converted to AD-type dementia [4].…”
Section: Interpretation Of Ad Biomarker Scoresmentioning
confidence: 99%